2010
DOI: 10.1029/2010jc006345
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐induced velocities inside a model seagrass bed

Abstract: [1] Laboratory measurements reveal the flow structure within and above a model seagrass meadow (dynamically similar to Zostera marina) forced by progressive waves. Despite being driven by purely oscillatory flow, a mean current in the direction of wave propagation is generated within the meadow. This mean current is forced by a nonzero wave stress, similar to the streaming observed in wave boundary layers. The measured mean current is roughly four times that predicted by laminar boundary layer theory, with mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
283
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(309 citation statements)
references
References 67 publications
17
283
2
Order By: Relevance
“…For experiments without kelp, the correlation between horizontal and vertical wave orbital velocities Sũ uw wT was consistent with a partial standing wave due to a slight wave reflection from the downstream end of the flume. We were unable to determine from the measurements whether the model kelp caused a significant change in the wave stress gradient that could affect the current, like that described in Luhar et al (2010).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For experiments without kelp, the correlation between horizontal and vertical wave orbital velocities Sũ uw wT was consistent with a partial standing wave due to a slight wave reflection from the downstream end of the flume. We were unable to determine from the measurements whether the model kelp caused a significant change in the wave stress gradient that could affect the current, like that described in Luhar et al (2010).…”
Section: Resultsmentioning
confidence: 97%
“…As the drag parameter aK D / v increases, the magnitude of G decreases only slightly but the phase of G is shifted, resulting in phase shifts in wave orbital velocities. If phase shifts in vertical and horizontal orbital velocity components are different, kelp drag could cause an effective wave stress, Sũ uw wT, that affects currents (Luhar et al 2010).…”
Section: Lsũmentioning
confidence: 99%
“…The force balance that determines in-canopy velocities depends on 3 factors: a shear stress imposed at the top of the canopy, drag exerted by the canopy, and -when waves are present -the inertial forces associated with that unsteadiness (Lowe et al 2005a, Luhar et al 2010. Luhar et al (2010) applied and streamlined the full rigid-canopy momentum balance model introduced by Lowe et al (2005a) to the case of a model canopy comprised of flexible elements.…”
Section: Canopy Flow Modelmentioning
confidence: 99%
“…Luhar et al (2010) applied and streamlined the full rigid-canopy momentum balance model introduced by Lowe et al (2005a) to the case of a model canopy comprised of flexible elements. In each of these approaches, canopy depth-averaged flow (Û) is described relative to undisturbed abovecanopy flow (U ∞ ) with the velocity ratio:…”
Section: Canopy Flow Modelmentioning
confidence: 99%
“…Recent experimental approaches (i.e. : Luhar et al, 2010) have revealed that the wave induced orbital velocity within the canopy was not significantly damped, revealing a relevant vertical motion within the plant field, pointing out the necessity of considering such aspect in the modeling.…”
Section: Introductionmentioning
confidence: 99%